Environment and activities of Audit Committees. Background of committee members and trust in financial information - Guðbjartsson, Einar; Snorrason, Jón Snorri (Research in applied business and economics, 2017)
The aim of this paper is to report partial results of a study on the environment and practices of audit committees in Iceland. The findings of two surveys, one from 2012 and the other from 2016, are compared. The paper identifies, among other things, education of committee members, reliance on financial informatin and the emphasis of audit committees. In the Annual Accounts Act, no. 3/2006, it is required for certain legal entities, public interest entities, according to the Act of Auditors, no. 79/2008, to establish an Audit Committee. The purpose of the audit committee is to ensure the high quality and high reliability of financial reporting and financial information. It does not matter whether the reports are for the administrators of the entity or the stakeholders outside the entity. The Annual Accounts Act, no. 3/2006, provides that the board constitute an audit committee. The aim of this paper is to disclosure partition of gender, education of members and changes in trust regarding financial reports according to audit committee’s members. The surveys were done among the leading companies and institutions of Iceland (which fall within the definition of “public interest entities”). The overall view is how audit committee´s issues are handled. This is the first study of its kind, which specifically look at committees in Iceland. Markmið þessarar greinar er að greina frá hluta niðurstaðna rannsóknar á umhverfi og starfsháttum endurskoðunarnefnda, nánar tiltekið bakgrunni nefndarmanna, áherslum þeirra og mati á trausti og gagnsæi fjárhagsupplýsinga. Bornar eru saman niðurstöður tveggja kannana höfunda á efninu, annars vegar frá árinu 2012 og hins vegar frá árinu 2016. Í lögum nr. 3/2006 um ársreikninga eru gerðar kröfur um að tilteknir lögaðilar, einingar tengdar almannahagsmunum, skv. lögum nr. 79/2008 um endurskoðendur, setji á stofn endurskoðunarnefnd. Tilgangur endurskoðunarnefnda er að tryggja gæði og áreiðanleika fjárhagsskýrslna og fjárhagsupplýsinga, hvort sem um er að ræða skýrslur til stjórnenda ...